2005
DOI: 10.1128/jcm.43.11.5588-5592.2005
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of the Dominant Human Fecal Microbiota upon Short-Course Antibiotic Challenge

Abstract: Recent studies have shown that the human fecal microbiota is composed of a consortium of species specific to the host and resistant to modifications over time. Antibiotics are known to affect the intestinal microflora, and ensuing changes may result in antibiotic-associated diarrhea. It is therefore important to characterize the nature and amplitude of these modifications and the ability of this ecosystem to return to its original profile-i.e., its resilience. Six healthy volunteers received oral amoxicillin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
174
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(187 citation statements)
references
References 29 publications
8
174
1
4
Order By: Relevance
“…It is known that antimicrobial agents not only affect the pathogens to which they are directed but may also impact other members of the intestinal microbiota (Sjö lund et al, 2003;De La Cochetiere et al, 2005). Thus they inhibit susceptible organisms and select for resistant ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that antimicrobial agents not only affect the pathogens to which they are directed but may also impact other members of the intestinal microbiota (Sjö lund et al, 2003;De La Cochetiere et al, 2005). Thus they inhibit susceptible organisms and select for resistant ones.…”
Section: Introductionmentioning
confidence: 99%
“…Thus they inhibit susceptible organisms and select for resistant ones. A number of different molecular fingerprinting techniques have previously been used to analyse the impact of antibiotics on the faecal microbiota such as denaturing or temperature gradient gel electrophoresis (DGGE or TGGE) (Donskey et al, 2003;Harmoinen et al, 2004), temporal TGGE (TTGE) (De La Cochetiere et al, 2005), terminal restriction fragment length polymorphism (T-RFLP) (Jernberg et al, 2005;Engelbrektson et al, 2006) and denaturing high-performance liquid chromatography (DHPLC) (Goldenberg et al, 2006). These techniques all bypass the necessity for cultivation, enabling comparative analyses of community fingerprints and the ability to monitor relative shifts in specific populations.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the difficulty to identify the exact profile at equilibrium has already been discussed [6], to take into account every patient's data including factors such as age, sex, clinical and/or antibiotherapy, is rather difficult. It needs the help of an abstract model that uses mathematical language to describe the behavior of the system by a set of variables and a set of equations that establish relationships between the variables.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, only a limited number of studies has assessed the prolonged impact of antibiotic treatment on gut microbiota. Recently, de la Cochetière et al (2005) reported a decrease in temporal temperature gradient gel electrophoresis profile similarities after 5-day oral administration of amoxicillin (500 mg 3 Â daily), confirming changes in the human fecal bacterial community.…”
mentioning
confidence: 97%
“…Although another band (g), indicative of a butyrate-producing bacterium, was only observed in two of the treated animals, our results overall indicated a strong negative effect of parenteral long-acting amoxicillin on butyrate-producing populations related to Roseburia species. Interestingly, de la Cochetière et al (2005) observed an appearance of bands matching other Clostridium cluster XIVa bacteria, Clostridium nexile and Ruminococcus torques 3 and 4 days after commencing antibiotic treatment, which were absent before amoxicillin was introduced and after the end of the treatment, on days 30 and 60. This apparent effect of amoxicillin treatment on individual populations of butyrate producing bacteria in colon has not been previously investigated and should be the subject of further studies aiming at its functional implications for the developing gut ecosystem.…”
mentioning
confidence: 99%